The Rhetoric of Affirmative Resistance - Wolfreys, Julian. author. aut Link
X, 235 p.
Keywords: In this wide-ranging, challenging theoretical study, Julian Wolfreys offers close readings of films, novels and poetry in order to draw attention to the ways in which texts resist acts of reading by performing their own idiomatic, wayward identities. Looking at the construction of identity in Lewis Carroll, Charlotte Perkins Gilman, James Joyce, Maya Deren, Sylvie Germain, Jacques Derrida, Michel Deguy, and George Eliot, Wolfreys asks the reader to reassess the textual performance of identity by attending to a rhetoric which is simultaneously both resistant to mastery and affirmative of dissonance.